Effect of E-Commerce Models on Financial Sustainability of Deposit Money Banks in Akure, Nigeria - Bedu, Adenike Adekiitan; Abayomi , Muftau Adesina; Ajayi , Modupe Olayinka (Archives of Business Research, 2022)
It is a widely held belief that adequate and appropriate technology infrastructure may determine the rate at which Deposit Money Banks (DMBs) in Nigeria leverage e-commerce for financial sustainability. This study investigated the effect of e-commerce models on financial sustainability of DMBs in Akure, Ondo State, Nigeria. The study adopted the survey research design. A multistage sampling procedure was used to select 200 respondents to whom the questionnaires were administered. The primary data obtained were subjected to both validity and reliability tests. Financial sustainability (proxied by net income growth) was used as the dependent variable, while accessibility, availability and usability of e-commerce models were the independent variables. Using the mean score, the study found that consumer-to-consumer, business-to-consumer, and business-to-business e-commerce models were all rated high in terms of accessibility, availability and usability. A multiple linear regression analysis showed that e-commerce models’ accessibility (β =0.161, p = 0.176); availability (β =0.139, p = 0.141); and usability (β = -0.017, p=0.874) did not individually exert a significant effect on financial sustainability. However, accessibility, availability and usability of e-commerce models jointly exerted a significant positive effect [F (3, 130) =5.226; p= .002] on financial sustainability of DMBs at 1% level in the study area. The study concluded that e-commerce models matter towards financial sustainability of DMBs. Finally, the study recommended that the accessibility, availability, and usability of e-commerce models should be continually strengthened in order to enhance their joint effect on financial sustainability of DMBs. Furthermore, the management of DMBs should focus on other critical success factors for achieving financial sustainability of DMBs in the study area.